A study of restorative potential in window views adopting Kaplan’s attention restoration theory and urban visual preferences defined by Lynch - Koprivec, Ljudmila; Zbašnik-Senegačnik, Martina; Kristl, Živa (Journal of Architecture and Urbanism, 2022)
Window views can enable restorativeness. Previous studies define characteristics of natural environment that trigger restorativeness, but fewer studies are dealing with restorative characteristics of urban environment. The purpose of this study is to identify qualities that enable restorativeness in natural and urban window views. Using a questionnaire survey as a method for obtaining the research data, responses of architectural students are analysed. To identify restorative potential in window views evaluation method according to Kaplan’s Attention Restoration Theory (ART) is used. Additional evaluation method for urban views is applied using Lynch’s theory of designing urban space that people can enjoy. Our findings show that urban views can be analysed according to Lynch’s visual qualities to identify the restorative potential of urban environments. Our findings also show that Lynch’s criteria may coincide with Kaplan’s criteria for assessing restorativeness. To define restorative potential in urban views in an early design phase, new evaluation methods are needed to transcend the renowned Kaplan’s Attention Restoration Theory into more approachable design mechanisms for designers and decision makers. Well-being of the inhabitants in a future dense urban environment will only be provided with an adequate window view.